A Critical Discourse Analysis of The Advertisement of Japanese Beauty Products - Eka Marthanty Indah Lestari (IZUMI, 2020)
This research analyzes the advertisement of Japanese beauty products through perspective of the critical discourse analysis as stated by Fairclough (1995). The discussed issues are linguistic features used in the advertisement of Japanese beauty products and the strategies used by advertisers to manipulate consumers who are women. Through three dimensions of the critical discourse analysis, it is known that the choices of vocabularies, grammar, modality, and rhetoric serve to bring psychological effect to consumers. Besides, the strategies used by advertisers to manipulate consumers for purchasing or using the offered products are puffery (exaggerating the quality of product), social proof (showing that their products are popular), liking (posting the positive reviews by celebrities for the related products), scarcity (limiting the quantity of product), emotional appeals (playing with the emotion of consumers), and scientific evidence (showing the scientific evidence). Analysis shows the result that advertisement is made based on the beauty myth in society. Besides, advertisement plays a role in creating and propagating the beauty myth in society.